POTENTIAL OF WULUH LEAVE (Averrhoal bilimbi L.) AS ANTIFUCIAL Candida albicans - Weni Astari; Elisa Putri (JBIO: jurnal biosains (the journal of biosciences), 2022)
Wuluh starfruit in Aceh commonly called "Boh Limeung" is a plant that is very often encountered, because star fruit is one of the spices in cooking. The Acehnese use star fruit as "SUNTI ACID", which is star fruit that is dried and then salted and used as a spice in cooking. The chemical compounds in star fruit leaves are flavonoids, saponins, sulfur, formic acid, steroid peroxides and tannins which are able to inhibit microbial activity and damage cell membranes so that, they can inhibit bacterial growth. The purpose of this study was to determine the potential of starfruit leaves (Averrhoal bilimbi L.) as antifungal candida albicans. The method used in this research is experimental laboratory. The treatments given in this study were 30%, 40%, 50%, 60% methanol extract concentrations. Then for the positive control (+), ketoconazole was used and for the negative control (-) aquadest was used. Based on the results obtained from the methanol extract of starfruit leaves (Averrhoal bilimbi L.) at concentrations of 30%, 40%, 50%, 60%, the average inhibition zone values were 17.5 mm, 17.35 mm, 17.95. mm, 18.77 mm. In Table 4.2, it can be seen that the largest inhibition zone is in the positive control (+) which is 23.5 mm while the negative control (-) is 0 mm.